Частотный метод контроля качества гальванопокрытий - Безотосный, В.Ф.; Козлов, В.В.; Набокова, О.В. (Електротехніка і електромеханіка, 2011)
The questions of the control of non-electrical and electrical parameters of materials by electromagnetic methods are considered in this article. The system of the automatic non-destroying control of mechanical pressures in the details of the radioelectronical equipment is offered.